Non-Communicable Diseases among the Elderly in Indonesia in 2018 - Rukmini Rukmini; Adianti Handajani; Astridya Paramita; Pramita Andarwati; Agung Dwi Laksono (Indian Journal of Forensic Medicine & Toxicology, 2022)
Non-Communicable Disease (NCD) is closely related to the aging process, social development, and increased risk factors. The study aims to analyze the prevalence of NCD among the elderly in Indonesia based on demographic characteristics. The study employed the 2018 Indonesia Basic Health Survey data. The survey used the multi-stage cluster random sampling method; it was a weighted sample of 85,358 elderly. In this analysis, the NCDs prevalence in the elderly includes hypertension, heart disease, bronchial asthma, chronic renal failure, diabetes mellitus (DM), stroke, and cancer determined based on a doctor’s diagnosis. The study result shows the prevalence of NCD in the elderly population in Indonesia, most of which are hypertension, mental-emotional disorders, depression, DM, and heart disease. Based on age group, the prevalence of hypertension, mental-health disorders, and depression tends to increase with increasing age, stroke and bronchial asthma are higher in the 70-79. DM and cancer were higher in the 60-69. Heart disease and kidney failure did not differ relatively between age groups. The prevalence of hypertension, mental-emotional disorders, depression, DM, heart disease, and cancer was higher in women. Still, asthma, stroke, and chronic kidney failure tended to be more in men. The study concluded that the most prevalent NCDs among older people in Indonesia were hypertension, mental, emotional disorders, depression, DM, and heart disease. NCDs have demographic characteristics.